Analysis of the Impact of Digitalization of Payments on the Preparation of Financial Reports in MSMEs in Lakarsantri District - Nanda Putri Widianti; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2024)
The rise of digital-based financial service platforms that help MSMEs as a sales transaction tool has many benefits for MSMEs, one of which is making it easier to prepare financial reports based on EMKM SAK because the digital payment system is able to store sales recaps accurately. The use of financial service platforms is also used by several MSME players in Lakarsanti District, Surabaya. For this reason, the author's aim is to analyze whether the use of digitalization of the payment system affects the preparation of financial reports in MSMEs in Lakarsantri District. Qualitative research with descriptive analysis methods. Also, semi-structural interviews were conducted with MSME business actors in Lakarsantri District. The results of this research are that many MSMEs in Lakarsantri District already use digital payment systems, but there are still many MSMEs that do not prepare financial reports. There are MSMEs that carry out simple financial records manually, only recording income and expenditure information, which is far from following EMKM SAK. And several MSMEs that have used digital payment systems and carried out simple financial records have felt helped by accurate transfers and transaction recaps.